Mycobacterium tuberculosis acg gene is required for growth and virulence in vivo. - Yanmin Hu; Anthony R M Coates (PLoS ONE, 2011)
Mycobacterium tuberculosis dosRS two-component regulatory system controls transcription of approximately 50 genes including hspX, acg and Rv2030c, in response to hypoxia and nitric oxide conditions and within macrophages and mice. The hspX lies between acg and Rv2030c. However, the functions of the dosR regulated genes in vitro and in vivo are largely unknown. Previously, we demonstrated that deletion of hspX gene produced a mutant which grew faster in macrophages and in mice. In this study, we attempted to determine the functions of acg and Rv2030c by gene inactivation. We demonstrate that Rv2030c is dispensable for virulence and growth. However, deletion of acg produced a mutant which is attenuated in both resting and activated macrophages and in acute and persistent murine infection models. Surprisingly, deletion of acg did not compromise the viability of the mutant to nitrosative and oxidative stresses in vitro and in vivo. In addition, when the WT and the acg mutants were treated with antibiotics such as the prodrugs nitrofurantoin and nitrofuran, the acg mutant became more sensitive than the WT strain to these drugs. This suggests that Acg may not function as a nitroreductase. These data indicate that acg encodes an essential virulence factor for M. tuberculosis and enables it to grow and survive in macrophages and in mouse organs.